+0  
 
0
353
2
avatar

(Cos(x) + iSin(x))^9

Guest Feb 20, 2015

Best Answer 

 #2
avatar+91436 
+5

$$(Cos(x) + iSin(x))^9 = e^{ix}^9=e^{9xi}$$

 

Using Euler's formula       

 

I think Geno's answer is correct too.  :)

Melody  Feb 21, 2015
Sort: 

2+0 Answers

 #1
avatar+17711 
+5

Using the expansion of  (x + y)9  

=  x9 + 9x8y + 36x7y2 + 84x6y3 + 126x5y4 + 126x4y5 + 84x3y6 + 36x2y7 + 9xy8 + y9

[Cos(x) + iSin(x)]9  =

=  Cos(x)9 + 9 Cos(x)i Sin(x) + 36 Cos(x)7 i2 Sin(x)2 + 84 Cos(x)i3 Sin(x)3 

    + 126 Cos(x)i4 Sin(x)4 + 126 Cos(x)i5 Sin(x)5 + 84 Cos(x)i6 Sin(x)6 

    + 36 Cos(x)i7 Sin(x)7 + 9 Cos(x) i8 Sin(x)8 + i9 Sin(x)9

Since:     i2 = -1    i3 = -i     i4 = 1    i5 = i     i6 = -1     i7 = -i    i8 = 1     i9 = i

=  Cos(x)9 + 9 i Cos(x)Sin(x) - 36 Cos(x)7 Sin(x)2 - 84 i Cos(x)Sin(x)3 

    + 126 Cos(x)Sin(x)4 + 126 i Cos(x)Sin(x)5 - 84 Cos(x)Sin(x)6 

    - 36 i Cos(x)Sin(x)7 + 9 Cos(x) Sin(x)8 + i Sin(x)9

geno3141  Feb 21, 2015
 #2
avatar+91436 
+5
Best Answer

$$(Cos(x) + iSin(x))^9 = e^{ix}^9=e^{9xi}$$

 

Using Euler's formula       

 

I think Geno's answer is correct too.  :)

Melody  Feb 21, 2015

22 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details